Translokacja siatkówki w wysiękowej postaci starczego zwyrodnienia plamki - Figurska, Małgorzata; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The paper presents different techniques of macular translocation in exudative form of AMD, including particularly retinal detatchment followed by retinotomy, limited macular translocation with chorioscleral infolding and outfolding by scleral imbrication.